1995
DOI: 10.1097/00054725-199509000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pericarditis Complicating Ulcerative Colitis

Abstract: : Pericarditis occurs rarely in association with inflammatory bowel disease. Because life-threatening complications may occur, pericarditis should be suspected in patients who present with chest symptoms. We report the case of a 28-year-old patient with ulcerative colitis who presented with pericarditis during an active disease exacerbation. The patient responded well to steroids and was discharged in good condition on day 9 after admission to the hospital. A review of the previously reported cases of pericard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In all, a review of the literature failed to produce a report of a patient <18 years of age with a pericardial effusion attributable solely as an extraintestinal manifestation of IBD. In addition, nearly 80% of IBD‐associated pericarditis and pericardial effusions are treated with corticosteroids (28). The patient in this case, however, developed a pericardial effusion despite taking prednisone for >3 weeks before her presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, a review of the literature failed to produce a report of a patient <18 years of age with a pericardial effusion attributable solely as an extraintestinal manifestation of IBD. In addition, nearly 80% of IBD‐associated pericarditis and pericardial effusions are treated with corticosteroids (28). The patient in this case, however, developed a pericardial effusion despite taking prednisone for >3 weeks before her presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac involvement is an accepted extraintestinal manifestation of IBD, pericarditis is rarely reported. Hinterreiter et al (28) described 39 reported cases of cardiac involvement believed to be related to IBD during the past 30 years. Of these 39 patients, 28 were taking sulfasalazine at the time they developed pericarditis.…”
Section: Discussionmentioning
confidence: 99%